PENDIDIKAN ISLAM PROGRESIF MUHAMMAD IQBAL - Yunita Furi Aristyasari (Al Ghazali, 2019)
This writing explores progressivism aspects in Sir Muhammad Iqbal's thought and attempts to construct educational system based on his ideas. As it is known that one important problem in Indonesia is the loss of Indonesian identity as indicated by the moral and spiritual fading. Long time ago, Muhammad Iqbal had felt similar unrest about the problem and finally led to his progressive ideas. This study belongs to library research using literature methodology. The study analyses Muhammad Iqbal's ideas with the progressivism philosophy. The results show that Iqbal’s thoughts indicated that he was a progressive person. However, the basis and estuary of Iqbal’s progressivism thought is different from the West’s. Iqbal's progressivism stems from faith and leads to the position of man as God's representative. As an effort to renew education, it is necessary to build an education system that aims to create a perfect human being by utilizing his potential